The reverse of the medal eaudiobook - O'Brian, Patrick (Aubrey & Maturin, 2012)
Captain Jack Aubrey, R. N., ashore after a successful cruise, is persuaded by a casual acquaintance to make certain investments in the City. This innocent decision ensnares him in the London criminal underground and in government espionage-the province of his friend Stephen Maturin. Is Aubrey's humiliation and the threatened ruin of his career a deliberate plot? This dark tale is a fitting backdrop to the brilliant characterization and sparkling dialogue which O'Brian's readers have come to expect.